Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

4(v+7) = -6(3v-4) +8v


Sagot :

Answer:

v=−27

Step-by-step explanation:

Since v is on the right side of the equation, switch the sides so it is on the left side of the equation.

−6(3v−4)+8v=4(v+7)

Simplify −6(3v−4)+8v

−10v+24=4(v+7)

Simplify 4(v+7).

−10v+24=4v+28

Move all terms containing v to the left side of the equation.

−14v+24=28

Move all terms not containing v to the right side of the equation.

−14v=4

Divide each term by −14 and simplify.

v=−27

The result can be shown in multiple forms.

Exact Form:

v=−27